The chromatin remodeling factor ISW-1 integrates organismal responses against nuclear and mitochondrial stress - Olli Matilainen (Nature Portfolio, 2017)
Changes in chromatin structure have been linked to organismal ageing. Here the authors show that altered histone expression and mitochondrial stress during C. elegans development result in chromatin changes and a cytosolic stress response that affects organismal longevity, and depends on HSF-1 and the chromatin remodeller, ISW-1.